ERKIN VOHIDOV SHE’RIYATIDA FALSAFIY TAFAKKUR VA YUMOR (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This article analyzes the artistic and philosophical dimensions of Erkin Vohidov’s poetry. The study explores how philosophical reflection and humor coexist harmoniously in his works. Through poetic expression, Vohidov contemplates human existence, morality, good and evil, and the meaning of life. His artistic philosophy encourages readers to reflect on moral values and the human condition.